From Aesop to Reynard beast literature in medieval Britain - Mann, Jill. (Oxford : Oxford University Press, 2009)
What do stories about animals have to tell us about human beings? This book analyzes the shrewd perceptions about human life - and especially human language - that emerge from narratives in which the main figures are 'talking animals'.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism; French literature -- To 1500 -- History and criticism; Latin literature, Medieval and modern -- History and criticism; Animals in literature; Animals, Mythical, in literature